Justin Case : shells, smells, and the horrible flip-flops of doom - Vail, Rachel; Cordell, Matthew, 1975- (New York : Feiwel and Friends, 2012)
"Justin is going to start fourth grade-but first, he has to survive the summer. He "gets" to go to camp every day on a bus. He "gets" to experience all sorts of new things: Bugs. Mess hall food. Flip-flops (they hurt the space between his toes and they're hard to walk in). And (gulp!) swimming. Justin's little sister, Elizabeth, seems to deal with camp just fine. So do his friends. Justin is trying very hard not to be a worried kid anymore, especially when it comes to making friends at camp, including a new kid who is kind of...rough. After all, Justin is going to be in fourth grade. It's time to be brave. Right?"--Dust jacket.
Keywords: Camps -- Fiction; Summer -- Fiction; Worry -- Fiction